Impact of UV-irradiation on electrical impedance spectroscopy of benign nevi: study protocol for a prospective, controlled, clinical study - Müller-Christmann, Christine; Schweizer, Anissa; Uhlmann, Lorenz; Hänßle, Holger (BMJ open, 2017)
Introduction: The clinical and histological changes of nevi after ultraviolet (UV) irradiation have been studied in detail. In contrast, the impact of UV irradiation on electrical impedance spectroscopy scores of nevi has not been investigated. However, for physicians, it is essential to know the extent to which changes in electrical impedance spectroscopy scores of nevi may be attributed to seasonal effects of UV irradiation. Methods: This is a prospective, controlled, clinical study evaluating the impact of UV irradiation on the electrical impedance spectroscopy scores of benign nevi in 50 patients undergoing phototherapy. To this end, benign nevi of patients with a medical indication for phototherapy will be measured by electrical impedance spectroscopy before, during and after UV irradiation. At the same time, non-irradiated nevi of the same patient will be measured to account for changes over time that are independent of direct UV irradiation. Ethics and dissemination: Ethical approval was obtained from the ethics committee of the medical faculty of the University of Heidelberg (ethics approval number S-279/2017). The design and the final results of the study will be published and made available to the public. Trial registration number DRKS00012456; Pre-results.